(untitled) (Patan Pragya, 2023)
This paper has encompassed the practices of foreign policies in relation to the international law as accorded in different international organizations validated by the members of nation-states. International law is a set of rules, principles, and standards which regulate the international relations between and among states. Foreign policy making refers to the formulations of the norms, values, and guidelines of how concerned sovereign states conduct their relations with other sovereign states. It is assumed that international law has been developing since the development of human society. In modern times international law has been developed based on the Code of Hammurabi, Magna Carta (1215), the Westphalia Treaty (24 October 1648), and dozens of modern international laws. The influence of international law in the formulation of the foreign policy of sovereign states started in ancient times. However, it became influential only after the development of the concept of the modern sovereign states. This study has focused on the influence of international law in the foreign policymaking of state. The particular sovereign states have their guidelines about their foreign policy. In addition, the particular state has its distinct conception of the domestication of international laws. Therefore, the influence of international law on the foreign policy of any sovereign state depends upon the process of domestication of international law by that particular state. In the modern era, most sovereign states are also state parties to international laws. Hence, the foreign policy of most modern states has been influenced by the international law. This study has focused on the influence of international law in the foreign policymaking of a sovereign state.